235k views
0 votes
Solve the equation
5(-4a+8)-5(6a-5)=15

2 Answers

3 votes

We can factor 5 at the left hand side:


5[(-4a+8)-(6a-5)]=15

Divide both sides by 5:


(-4a+8)-(6a-5)=3 \iff -4a+8-6a+5 = 3

Sum like terms:


-10a+13=3

Subtract 13 from both sides:


-10a=-10

Divide both sides by -10:


a=1

User StuStirling
by
5.0k points
5 votes

Step 1: Simplify both sides of the equation.

5(−4a+8)−5(6a−5)=15

(5)(−4a)+(5)(8)+(−5)(6a)+(−5)(−5)=15

−20a+40+−30a+25=15

(−20a+−30a)+(40+25)=15

−50a+65=15

−50a+65=15

Step 2: Subtract 65 from both sides.

−50a+65−65=15−65

−50a=−50

Step 3: Divide both sides by -50.

-50a/-50=-50/-50

Therefore, the answer would be a=1.

User Seldo
by
4.9k points